2016
DOI: 10.1080/13218719.2016.1230923
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Responsivity among Violent Offenders: Predicting Access to Treatment, Treatment Engagement and Programme Completion

Abstract: This retrospective archival study examines whether pre-treatment responsivity characteristics influence access to, engagement in, and completion of a violent offender treatment programme. The participants are 115 violent offenders referred for a group-based multimodule treatment programme in medium-and high-security correctional facilities in Victoria, Australia. The case files for each participant were reviewed and information regarding responsivity factors and responses to treatment were gathered. Responsivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
9
1
Order By: Relevance
“…Since neurofeedback training aims directly at changing basic neurophysiological brain functioning, it is less dependent on direct patient-therapist interaction than traditional psychotherapeutic interventions (Casher, 2013). Patients' motivation and compliance for psychotherapy tends to be especially low in forensic psychiatric populations (O'Brien & Daffern, 2017;Ogloff, Wong, & Greenwood, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Since neurofeedback training aims directly at changing basic neurophysiological brain functioning, it is less dependent on direct patient-therapist interaction than traditional psychotherapeutic interventions (Casher, 2013). Patients' motivation and compliance for psychotherapy tends to be especially low in forensic psychiatric populations (O'Brien & Daffern, 2017;Ogloff, Wong, & Greenwood, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who have a history of violent offending are commonly considered to be at a high risk of reoffending (Nadesu, 2009;O'Brien & Daffern, 2017). Nadesu (2009) reported that, of those individuals who have already been imprisoned for violent offences, 64% were re-imprisoned for another violent offence within a 60-month period.…”
Section: Treatment Of Violent Offendingmentioning
confidence: 99%
“…Maladaptive personality traits might reduce individuals' ability to fully engage in treatment. For example, psychopathic personality traits and borderline personality traits are associated with poorer engagement in treatment, superficial progress and higher attrition rates (McCarthy & Duggan, 2010;O'Brien & Daffern, 2017;Romero-Martínez et al, 2016;Schroeder et al, 2013). Furthermore, psychopathic traits (e.g., callous-unemotional and aggression) in individuals with violent offences have been shown to reduce the efficacy of THE ROLE OF PERSONALITY FACTORS 14 correctional treatment programmes (Kolla et al, 2014) and are, as such, considered a responsivity issue (Olver & Wong, 2011).…”
Section: Maladaptive Personality Traits and Treatment Of Violent Offendingmentioning
confidence: 99%
See 2 more Smart Citations